An integrated power generation plan considering carbon emission constraint - Koopman, Sabrina (University of the Witwatersrand, Johannesburg, 2024)
In the context of South Africa's energy crisis, this research report examines the optimization of South Africa's power generation system, considering coal, onshore wind, and solar PV technologies within a carbon emissions constraint. The primary objective is to minimise costs while addressing the urgent need for sustainable energy solutions in a country heavily reliant on coal-fired power. The methodology comprises two main components: system modelling of solar and wind generation, and a mathematical framework featuring cost minimization as the objective function with a power balance constraint and a carbon emissions constraint as the two key constraints. This approach allows for a comprehensive analysis of potential energy mixes that balance economic and environmental concerns. The study's findings indicate that a more sustainable and balanced energy mix is achievable in South Africa through significant expansion of renewable energy capacities. While this transition requires substantial short-term investment and infrastructure development, it offers long-term benefits including reduced carbon emissions and enhanced energy system resilience. The optimization results suggest that further integration of renewable energy technologies is possible, albeit at a higher cost. The research highlights the increasing cost-effectiveness of renewable energy and emphasises the importance of capitalising on this trend in emerging markets like South Africa. In conclusion, this thesis demonstrates that South Africa can significantly reduce its carbon emissions within the next five years by improving its energy mix through increased integration of renewable energy generation technologies. These insights are crucial for policymakers, industry stakeholders, and researchers in shaping South Africa's future energy landscape and contributing to global climate change mitigation efforts.
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce (Economics/Economic Science) in the School of Economics and Finance, University of the Witwatersrand, Johannesburg 2024
Keywords: Power Generation; Carbon Emissions; South Africa; Energy Mix; Renewable Energy; Objectve Function; Constraints; SDG-7: Affordable and clean energy